1998
DOI: 10.1111/j.1470-9856.1998.tb00127.x
|View full text |Cite
|
Sign up to set email alerts
|

The politics of social service provision through NGOs: A study of Latin America

Abstract: This article looks at the role of NGOs in social service delivery in Latin America and questions some of the assumptions which are often made about their abilities. Following the implementation of the neo-liberal model, increased conditionality has been placed on economic assistance. This has created a new role for NGOs, whereby they are harnessed by states in order to secure effective implementation of reform packages. In the process many NGOs find their own agendas become distorted. The paper discusses the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 25 publications
0
27
0
2
Order By: Relevance
“…The World Bank, for example, has a gender policy unit responsible for mainstreaming gender issues and has committed resources to developing 'woman friendly' policies; but a recent evaluation of 100 World Bank projects shows the results to be disappointing in this regard and concludes that gender issues were in fact 'widely neglected' in their design and implementation (Frances, 2001: 86). Likewise, Latin American studies of NGOs in a variety of countries have shown that it was rare to find gender inputs into the administration of Social Funds (Gideon, 1998). There is no reason to suppose that the same gap between stated intentions and project implementation will not occur in the case of social capital enhancing projects.…”
Section: Gender and Social Capitalmentioning
confidence: 99%
“…The World Bank, for example, has a gender policy unit responsible for mainstreaming gender issues and has committed resources to developing 'woman friendly' policies; but a recent evaluation of 100 World Bank projects shows the results to be disappointing in this regard and concludes that gender issues were in fact 'widely neglected' in their design and implementation (Frances, 2001: 86). Likewise, Latin American studies of NGOs in a variety of countries have shown that it was rare to find gender inputs into the administration of Social Funds (Gideon, 1998). There is no reason to suppose that the same gap between stated intentions and project implementation will not occur in the case of social capital enhancing projects.…”
Section: Gender and Social Capitalmentioning
confidence: 99%
“…Notwithstanding this scepticism (Cooke and Kothari, 2001;Gideon, 1998) many NGOs have played a positive role in the articulation of gender interests. Some Latin American feminist NGOs have been able to achieve a degree of organizational autonomy while at the same time collaborating with the state and its agencies to bring about reform on certain issues (Molyneux, 2001).…”
Section: Voicementioning
confidence: 99%
“…Of course, pure neo-liberalism has not been enacted in Latin America, but the consequences of freeing market forces and cutting public services have been impoverishment, unemployment, worse social indicators (malnutrition, infant deaths, disease) and insecurity. In tune with privatisation, NGOs -by definition private entities -have stepped into the social service breech but their assistance is based on specific projects which cover a certain time and place (Gideon, 1998). They do not contemplate universal coverage nor is their continuation guaranteed and so in no sense do they sustain social rights, despite their genuine commitment to improving people's lives.…”
Section: Challenging Citizenship and Continuing Client-shipmentioning
confidence: 99%